Engineering Optics 2.0 A Revolution in Optical Theories, Materials, Devices and Systems - Luo, Xiangang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides comprehensive information on the history and status quo of a new research field, which we refer to as Engineering Optics 2.0. The content covers both the theoretical basis and the engineering aspects in connection with various applications. The field of Engineering Optics employs optical theories to practical applications in a broad range of areas. However, the foundation of traditional Engineering Optics was formed several hundred years ago, and the field has developed only very gradually. With technological innovations in both the fabrication and characterization of microstructures, the past few decades have witnessed many groundbreaking changes to the bases of optics, including the generalizing of refraction, reflection, diffraction, radiation and absorption theories. These new theories enable us to break through the barriers in traditional optical technologies, yielding revolutionary advances in traditional optical systems such as microscopes, telescopes and lithography systems. .
Introduction -- Historical Review of Engineering Optics -- Fundamental theories of EO 2.0 -- Sub-diffraction-limited optics -- Flat optics -- Perfect absorption of light -- Polarization and orbital angular momentum -- Radiation and emission.
Keywords: Optical materials; Lasers; Telecommunication; Physics; Optical Materials; Laser; Microwaves, RF Engineering and Optical Communications; Classical and Continuum Physics